Rapid Determination of Per- and Polyfluoroalkyl Substances (PFAS) in Harbour Porpoise Liver Tissue by HybridSPE®–UPLC®–MS/MS - Simone Trimmel; Kristine Vike-Jonas; Susana V. Gonzalez; Tomasz Maciej Ciesielski; Ulf Lindstrøm; Bjørn Munro Jenssen; Alexandros G. Asimakopoulos (Toxics, 2021)
A rapid hybrid solid phase extraction (HybridSPE®) protocol tailored to ultra-performance liquid chromatography–electrospray ionization tandem mass spectrometry (UPLC®–ESI–MS/MS) analysis was developed for the determination of 15 per- and polyfluoroalkyl substances (PFAS) in liver tissue from harbour porpoises (Phocoena phocoena). The HybridSPE® technique has been applied in trace concentration bioanalysis, but it was mainly used for liquid biological media until now. In this study, the protocol was applied on tissue matrix, and it demonstrated acceptable absolute recoveries (%) ranging from 44.4 to 89.4%. The chromatographic separation was carried out using a gradient elution program with a total run time of 4 min. The inter-day method precision ranged from 2.15 to 15.4%, and the method limits of detection (LODs) ranged from 0.003 to 0.30 ng/g wet weight (w.w.). A total of 20 liver samples were analyzed to demonstrate the applicability of the developed method in liver tissue from a wildlife species.